WELDING TECHNOLOGY WITH THE USE OF VARIOUS ENERGY SOURCES - Vakulenko, I. O.; Plytchenko, S. O. (Science and Transport Progress, 2008)
The paper presents technologies of welding with the use of different energy sources.